Comparison of the Inhibitory Effect of Some Antibiotics with Silver Nanoparticles Agains Proteus Mirabilis Isolated from Urinary Tract Infection - Hussny, Hanan Askar (American Journal of Biology and Natural Sciences, 2026)
Urinary tract infections (UTIs) are caused by different types of Proteus and are one of the most common diseases. This disease is endemic in many influenza outbreaks, including Iraq. The aim of this study was to determine the prevalence of bacterial infections in females and males and compare their sensitivity to antibiotics and silver nanoparticles in infected individuals. This prospective cross-sectional study was conducted in the laboratory of the College of Basic Education, Sumer University, Iraq, during the period from January 2, 2025 to April 2025. Fifty urine samples were collected from all age groups, 25 males and 25 females. All isolates were confirmed to be Proteus by biochemical tests. Twenty (40%) tested positive for Proteus bacteria. Of these cases, 7 (35%) were males and 17 (65%) were females. The antibiotic resistance of these isolates was studied. The resistance pattern against different antimicrobials was as follows: ampicillin (100%), gentamicin and cefepime (50%), norfloxacin (40%) and amikacin (35%). The sensitivity of bacteria against silver nanoparticles was also studied at five different concentrations and was sensitive to the highest concentration and decreased at lower concentrations as follows: 0.1 (20 mm), 0.75 (19 mm), 0.05 (15 mm), 0.025 (12 mm), 0.001 (5 mm).